Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Pada Pokok Bahasan Ikatan Kimia Di Kelas X SMA Negeri 1 Sausu - Dewijayanti, Putu W.; Walanda, Daud K.; Solfarina, Solfarina (Jurnal Akademika Kimia, 2014)
Generally in the learning process students tend to be passive in finding out the concept. Students just rewrite the existing conceptss, so that their learning outcomes are less. To obtainthe improvement of students’ learning outcome it required a learning model, one of them is cooperative learning model TSTS. This study aims to apply student-centered in the learning process of SMA Negeri 1 Sausu, and to investigate the students’ learning outcomes with the application of the learning model TSTS type and the conventional on chemistry subject at the tenth grade students of SMA Negeri 1 Sausu. This research is experimental research with quasi experiment design. The population is the whole tenth grade students numbered 124 studends with the sample taken purposively where class B as for the control class numbered 31 students and class D as for the experimental class numbered 31 students. The results of the data analysis obtained the average score of the experimental class is 7.04 with deviation standard is 2.85 and control class is 5.43 with deviation standard is 3.11. from the results of testing hypothesis obtained tcounted = 2.26 and ttable = 2.00 at α = 0.05, so that H1 is accepted and H0 is rejected. These data showed that students’ learning outcomes with the implementation of cooperative learning model TSTS were higher than conventional learning model on the subject of chemistry at the tenth grade students of SMA Negeri 1 Sausu.